The effect of urban–rural health insurance integration on consumption of middle-aged and older adult households in rural areas: evidence from China - Wang, Lianjie; Hu, Qi (Frontiers in Public Health, 2023)
Introduction Rural consumption is crucial in promoting economic and social development in China’s economic slowdown. Integrating urban-rural residents’ health insurance has alleviated the financial burden of medical expenses for rural households and boosted rural household consumption. This study examines the effect of integrating urban–rural residents’ health insurance on the consumption patterns of middle-aged and older adult households in rural China. Our research provides a reference basis for improving rural healthcare security and enhancing the sustainable consumption capacity in rural areas. Methods We employed a Propensity Score Matching Difference-in-Differences model (PSM-DID) to estimate the association between health insurance integration and household consumption using panel data from the China Health and Retirement Longitudinal Study (CHARLS) from 2013 to 2018. Furthermore, we employed a mediation model to analyze the influencing mechanisms. Results Our findings suggested a positive association between health insurance integration and survival consumption as well as total consumption among rural middle-aged and older adult households. The conclusion remained valid after endogeneity treatment, robustness and placebo tests. Furthermore, we found that the impact of health insurance integration is more pronounced for middle-aged, female, and high-income rural residents’ households. Integrating urban–rural residents’ health insurance raised consumption by reducing medical expenses and increasing health and life expectancy. Discussion Policymakers should deepen the rural medical and health system reform, improve the convenience of medical services for middle-aged and older adult families in rural areas, and improve the medical and life assistance mechanism for vulnerable groups in rural areas. Additionally, the local government should continuously broaden rural household income channels to promote upgrading consumption structure while improving overall consumption levels.